Extending electron orbital precession to the molecular case: Use of orbital alignment for observation of wavepacket dynamics - Martay, H; England, D; McCabe, D; Walmsley, I (2011)
The complexity of ultrafast molecular photoionization presents an obstacle to the modeling of pump-probe experiments. Here, a simple optimized model of atomic rubidium is combined with a molecular dynamics model to predict quantitatively the results of a pump-probe experiment in which long-range rubidium dimers are first excited, then ionized after a variable delay. The method is illustrated by the outline of two proposed feasible experiments and the calculation of their outcomes. Both of these proposals use Feshbach Rb872 molecules. We show that long-range molecular pump-probe experiments should observe spin-orbit precession given a suitable pump pulse, and that the associated high-frequency beat signal in the ionization probability decays after a few tens of picoseconds. If the molecule was to be excited to only a single fine-structure state, then a low-frequency oscillation in the internuclear separation would be detectable through the time-dependent ionization cross section, giving a mechanism that would enable observation of coherent vibrational motion in this molecule. © 2011 American Physical Society.